High-heat-resistance glass fiber reinforced nylon material and preparation method thereof

By using heat-resistance-reinforced masterbatch and aramid fiber in glass fiber reinforced nylon materials, combined with aluminum hydroxide-melamine cyanurate flame retardant, the problem of insufficient heat resistance and thermal stability in high-temperature environments is solved. , achieving high strength, lightweight and heat resistance improvement, avoiding spontaneous combustion or ignition.

CN119161725APending Publication Date: 2024-12-20HANGZHOU ZETONG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411295288.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-17
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing glass fiber reinforced nylon materials have insufficient heat resistance and thermal stability in high-temperature environments, and cannot effectively deal with spontaneous combustion or ignition conditions, and cannot meet special performance needs such as high strength, lightweight and heat resistance.

Method used

Preparation by melting, extruding, cooling and cutting through a composite of zinc oxide and cage polysilsesquioxane in a twin screw extruder, combining aramid fibers and aluminum hydroxide-melamine Cyanurate flame retardant improves the heat resistance and flame retardant properties of the material.

Benefits of technology

It significantly improves the heat resistance and thermal stability of the material, avoids spontaneous combustion or ignition, and meets the good performance and high-strength and lightweight requirements in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161725A_ABST
    Figure CN119161725A_ABST
Patent Text Reader

Abstract

The invention discloses a high heat-resistant glass fiber reinforced nylon material and a preparation method, and relates to the technical field of high polymer materials, the high heat-resistant glass fiber reinforced nylon material comprises the following components by weight: 30-80 parts of nylon resin, 5-20 parts of glass fiber, 5-20 parts of aramid fiber, 10-20 parts of heat-resistant reinforced master batch, 10-20 parts of a flame retardant and other auxiliary agents, the preparation method comprises the following steps: mixing a styrene-acrylonitrile copolymer, polyphenyl ether, a lubricant, a stabilizer and long cut carbon fibers, mixing zinc oxide and polyhedral oligomeric silsesquioxane, adding heat-resistant reinforced master batches prepared by a twin-screw extruder, mixing, melting, extruding, cooling, drying and cutting to obtain a final product, namely the high-heat-resistant glass fiber reinforced nylon material. By adding the heat-resistant reinforced master batch, the strength, heat resistance and thermal stability of the nylon material are improved, and the problems that a traditional nylon material cannot work in a high-temperature environment and is poor in working performance are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, in particular to a high-heat-resistant glass fiber reinforced nylon material and a preparation method thereof. Background Art

[0002] In a society with rapid development of modern industry, nylon composite materials cover many fields such as automobiles, electronic and electrical, and engineering materials, and play an important role in various fields. However, simple nylon composite materials cannot meet the needs of various fields that are constantly expanding and developing. Glass fiber reinforced nylon materials are composite materials obtained by adding a certain amount of glass fiber to nylon resin. With the improvement of technology, the fields and environments that glass fiber reinforced nylon materials can adapt to have been improved. Glass fiber reinforced nylon materials are gradually replacing various metal materials in various fields, saving a lot of metal and energy. However, in many fields, there are still many environments that glass fiber reinforced nylon materials cannot adapt to. High temperature, high humidity, high corrosiveness and other environments seriously affect the working performance and service life of glass fiber reinforced nylon materials. In high temperature environments, the heat resistance and thermal stability of traditional nylon materials and ordinary glass fiber reinforced nylon materials are not enough to support their work. At the same time, it is very easy for materials to spontaneously combust or be ignited in high temperature environments. Traditional nylon materials cannot effectively deal with the occurrence of such emergencies.

[0003] Patent document CN105176079B discloses a chopped glass fiber reinforced nylon modified material and a preparation method thereof. The above patent realizes the modification by adding chopped glass fibers, thereby improving the heat resistance, dimensional stability, and rigidity of the nylon modified material, and significantly improving mechanical properties such as tensile strength and flexural strength, so that the nylon modified material has good wear resistance, heat resistance, oil resistance and chemical resistance, and also greatly reduces the water absorption and shrinkage of the nylon modified material, and has excellent dimensional stability and excellent mechanical strength. However, the above patent cannot achieve a significant improvement in the heat resistance of the nylon material, and cannot maintain good performance in a high-temperature environment.

[0004] Patent document CN102850783B discloses a nylon 6 / polypropylene composite material and its preparation method. This patent achieves a guaranteed effective length of glass fiber, thereby significantly improving the material's rigidity and strength, while also significantly enhancing its hydrolysis resistance and heat resistance. The fibers are evenly dispersed, and the weight of the finished product is stable. Furthermore, the invention allows for direct injection molding, resulting in high production efficiency, and the finished product can be recycled after pulverization, thus minimizing environmental pollution. However, this patent fails to address the insufficient thermal stability of the nylon material.

[0005] Patent document CN104419198B discloses a flame-retardant and antistatic continuous long glass fiber reinforced high-temperature resistant nylon composite material and its preparation method. The above patent achieves better mechanical properties, heat resistance and dimensional stability; the use of four-needle zinc oxide whiskers as an antistatic agent can not only enable the composite material to achieve an ideal antistatic effect, but also improve its mechanical properties and heat resistance, eliminating the adverse effects of the addition of flame retardants on the mechanical and heat resistance of the composite material. However, the above patent cannot be used in occasions with special performance requirements such as high strength, lightweight, and heat resistance.

[0006] Patent document CN105504795B discloses a heat-resistant and hydrolysis-resistant reinforced nylon composite material and its preparation method. This patent raises the heat resistance of nylon, enabling its long-term operating temperature to exceed 180°C. The heat-resistant functional masterbatch and hydrolysis-resistant glass fiber ensure that the reinforced nylon resin maintains excellent mechanical strength even in hot and humid environments. However, this patent fails to improve the thermal stability and flame retardancy of the material itself, preventing the problem of spontaneous combustion or ignition in high-temperature environments.

[0007] In summary, the above patents cannot achieve the function of improving the heat resistance of nylon materials and allowing nylon materials to work in high-temperature environments. They cannot achieve the function of improving the thermal stability of nylon materials and allowing nylon materials to maintain good performance in high-temperature environments. They cannot achieve the function of using nylon materials in situations where special performance requirements such as high strength, lightweight and heat resistance are required. They cannot achieve the function of self-flammability in the event of spontaneous combustion or ignition in high-temperature environments. As a result, high-heat-resistant glass fiber reinforced nylon materials cannot meet the performance requirements in the field of polymer material technology. To this end, the present application proposes a method that can improve the heat resistance of nylon materials and allow nylon materials to work in high-temperature environments, improve the thermal stability of nylon materials and allow nylon materials to maintain good performance in high-temperature environments, enable nylon materials to be used in situations where special performance requirements such as high strength, lightweight and heat resistance are required, and achieve self-flame retardant function in the event of spontaneous combustion or ignition in high-temperature environments, so that high-heat-resistant glass fiber reinforced nylon materials can meet the performance requirements in the field of polymer material technology. Summary of the Invention

[0008] The purpose of the present invention is to provide a high-heat-resistant glass fiber reinforced nylon material and a preparation method thereof, so as to solve the technical problems raised in the above-mentioned background technology that the heat resistance of the nylon material cannot be improved to allow the nylon material to work in a high-temperature environment, the thermal stability of the nylon material cannot be improved to allow the nylon material to maintain good performance in a high-temperature environment, the nylon material cannot be used in occasions with special performance requirements such as high strength, lightweight and heat resistance, and the nylon material cannot be self-flammed in the event of spontaneous combustion or ignition in a high-temperature environment, resulting in the high-heat-resistant glass fiber reinforced nylon material being unable to meet the performance requirements in the field of polymer material technology.

[0009] To achieve the above object, the present invention provides the following technical solution: a high heat-resistant glass fiber reinforced nylon material, comprising the following components by weight: nylon resin: 30 parts to 80 parts; Glass fiber: 5 to 20 parts; Aramid fiber: 5 to 20 parts; Heat-resistant reinforcing masterbatch: 10 to 20 parts; Flame retardant: 10 to 20 parts; Lubricant: 2 to 4 parts; Stabilizer: 2 to 4 parts; Catalyst: 1 to 3 parts; Coupling agent: 0.1 to 0.5 parts; The preparation method of the heat-resistant reinforcing masterbatch comprises: mixing zinc oxide and cage-type polysilsesquioxane to react, so that the cage-type polysilsesquioxane forms a coating layer on the surface of the zinc oxide, washing and drying the encapsulated composite of zinc oxide and cage-type polysilsesquioxane, removing unreacted raw materials, preparing sufficient amounts of styrene-acrylonitrile copolymer, polyphenylene ether, lubricant and stabilizer for mixing, placing the mixture and chopped carbon fibers into a twin-screw extruder, adding the composite of zinc oxide and cage-type polysilsesquioxane at a position where the internal temperature of the twin-screw extruder is between 220° C. and 245° C., and obtaining the heat-resistant reinforcing masterbatch through melting, extrusion, cooling, drying and cutting, wherein the partition control temperature of the twin-screw extruder (from the feed port to the die outlet) is 210° C., 245° C., 255° C., 245° C., 230° C., 230° C., 220° C. and 220° C., and the material residence time in the barrel is 2 minutes; In the process of preparing heat-resistant reinforcing masterbatch, although the composite of zinc oxide and cage-type polysilsesquioxane is wrapped by the cage-type polysilsesquioxane shell in a high-temperature environment, excessively high temperature will destroy its internal structure, resulting in an intensified agglomeration of the composite of zinc oxide and cage-type polysilsesquioxane, resulting in poor heat resistance and thermal stability of the prepared heat-resistant reinforcing masterbatch. Therefore, the temperature needs to be controlled not to be too high during the preparation process.

[0010] Preferably, the nylon resin is one or a mixture of PA6 and PA66.

[0011] Preferably, the glass fiber is alkali-free glass fiber, the aramid fiber is para-aramid fiber, and the weight ratio of the glass fiber to the aramid fiber is 1:1.

[0012] Preferably, the flame retardant is a mixture of aluminum hydroxide and melamine cyanurate, and the flame retardant properties of the material are improved and the generation of harmful substances is reduced by using two flame retardants with different action systems.

[0013] Preferably, the lubricant is a silicone masterbatch, which is used to improve the uniformity of the material and enhance the performance and service life of the material.

[0014] Preferably, the stabilizer is a copper salt masterbatch, which is used to prevent oxidative degradation during processing and improve the heat resistance of the material.

[0015] Preferably, the catalyst is ferric hydroxide, which catalyzes a specific reaction of the mixed material in a twin-screw extruder.

[0016] Preferably, the coupling agent is a silane coupling agent.

[0017] Preferably, the steps of the preparation method are as follows: Step 1: Prepare nylon resin, glass fiber and aramid fiber in the required proportions and dry them to remove moisture at a drying temperature of 50-80°C for 4 hours; Step 2: mixing the glass fiber and the aramid fiber in a weight ratio of 1:1 to obtain a mixed fiber; Step 3: Add nylon resin, flame retardant, lubricant, stabilizer and catalyst into a high-speed mixer, and fully mix all the materials in the high-speed mixer to obtain mixed material A; Step 4: Place the mixed material A into the twin-screw extruder through the main feed port, and place the mixed fiber into the twin-screw extruder through the side feed port. During the melting process, add the heat-resistant reinforcing masterbatch to the part of the twin-screw extruder where the internal temperature is between 220℃ and 245℃. After melt blending, extrude the mixture into the mold for shaping. Step 5: After the product is cooled and shaped, dry it; Step 6: Cut the molded product to obtain the final high heat-resistant glass fiber reinforced nylon material.

[0018] Preferably, when the glass fiber and the aramid fiber are mixed, a silane coupling agent is used to modify the surface of the glass fiber and the aramid fiber to improve their compatibility with the nylon resin and enhance the mechanical properties and durability of the composite material; The flame retardant is a mixture of melamine cyanurate and aluminum hydroxide. Before use, the aluminum hydroxide needs to be modified with a coupling agent to improve its dispersibility and mechanical properties in nylon. Treatment of melamine cyanurate requires drying at 100°C in a vacuum environment for 8 hours.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention improves the heat resistance of high heat-resistant glass fiber reinforced nylon materials by adding heat-resistant reinforcing masterbatch to the raw materials, solving the problem of insufficient heat resistance and inability to maintain good performance in high temperature environments; 2. The present invention is designed to add zinc oxide and cage-type polysilsesquioxane to the heat-resistant reinforcing masterbatch. After the addition of the two, the weather resistance and thermal stability of the heat-resistant reinforcing masterbatch itself are improved to a certain extent, thereby enhancing the heat resistance of the material itself in the preparation of high-heat-resistant glass fiber reinforced nylon materials, and solving the problem of insufficient thermal stability and heat resistance; 3. The present invention uses aramid fiber to replace part of the glass fiber. The addition of aramid fiber improves the mechanical properties of the material itself, broadens the application field of the material, and solves the problem that it cannot be used in situations requiring special performance such as high strength, lightweight, and heat resistance; 4. The present invention improves the thermal stability and flame retardancy of the material itself by designing a mixture of aluminum hydroxide and melamine cyanurate as a flame retardant, thereby avoiding the problem of spontaneous combustion or ignition in a high-temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the composition of the present invention; Figure 2 This is a schematic diagram of the preparation process of the high heat-resistant glass fiber reinforced nylon material of the present invention; Figure 3 This is a schematic diagram of the preparation process of the heat-resistant enhanced masterbatch of the present invention; DETAILED DESCRIPTION

[0021] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention. Example 1

[0022] See also Figure 1 、 Figure 2 and Figure 3, a high heat-resistant glass fiber reinforced nylon material, comprising the following components in parts by weight: nylon resin: 67 parts; Glass fiber: 5 parts; Aramid fiber: 5 parts; Heat-resistant reinforcing masterbatch: 15 parts; Flame retardant: 12 parts; Lubricant: 2 parts; Stabilizer: 2 parts; Catalyst: 3 parts; Coupling agent: 0.2 parts; The preparation method of the heat-resistant reinforcing masterbatch comprises: mixing zinc oxide and cage-type polysilsesquioxane to react, so that the cage-type polysilsesquioxane forms a coating layer on the surface of the zinc oxide, washing and drying the encapsulated composite of zinc oxide and cage-type polysilsesquioxane, removing unreacted raw materials, preparing sufficient amounts of styrene-acrylonitrile copolymer, polyphenylene ether, lubricant and stabilizer for mixing, placing the mixture and chopped carbon fibers into a twin-screw extruder, adding the composite of zinc oxide and cage-type polysilsesquioxane at a position where the internal temperature of the twin-screw extruder is between 220° C. and 245° C., and obtaining the heat-resistant reinforcing masterbatch through melting, extrusion, cooling, drying and cutting, wherein the partition control temperature of the twin-screw extruder (from the feed port to the die outlet) is 210° C., 245° C., 255° C., 245° C., 230° C., 230° C., 220° C. and 220° C., and the material residence time in the barrel is 2 minutes; During the preparation of heat-resistant reinforcing masterbatch, although the composite of zinc oxide and cage-type polysilsesquioxane is wrapped by the cage-type polysilsesquioxane shell in a high-temperature environment, excessively high temperature will destroy its internal structure, thereby causing the composite of zinc oxide and cage-type polysilsesquioxane to agglomerate, resulting in poor heat resistance and thermal stability of the prepared heat-resistant reinforcing masterbatch. Therefore, the temperature should be controlled not to be too high during the preparation process. The steps of the preparation method are as follows: Step 1: Prepare nylon resin, glass fiber and aramid fiber in the required proportions and dry them to remove moisture at a drying temperature of 50-80°C for 4 hours; Step 2: mixing the glass fiber and the aramid fiber in a weight ratio of 1:1 to obtain a mixed fiber; Step 3: Add nylon resin, flame retardant, lubricant, stabilizer and catalyst into a high-speed mixer, and fully mix all the materials in the high-speed mixer to obtain mixed material A; Step 4: Place the mixed material A into the twin-screw extruder through the main feed port, and place the mixed fiber into the twin-screw extruder through the side feed port. During the melting process, add the heat-resistant reinforcing masterbatch to the part of the twin-screw extruder where the internal temperature is between 220℃ and 245℃. After melt blending, extrude the mixture into the mold for shaping. Step 5: After the product is cooled and shaped, dry it; Step 6: Cut the molded product to obtain the final high heat-resistant glass fiber reinforced nylon material; Furthermore, in the raw material preparation stage, 60 parts of nylon resin, 12 parts of heat-resistant reinforcing masterbatch, 10 parts of flame retardant, 3 parts of lubricant, 3 parts of stabilizer, and 3 parts of catalyst were prepared, the nylon resin was dried at 80°C for 4 hours, and the materials except the heat-resistant reinforcing masterbatch were placed in a high-speed mixer and fully mixed to obtain mixed material A for standby use; 6 parts of glass fiber, 6 parts of aramid fiber and 0.4 parts of coupling agent are prepared, and the surfaces of the glass fiber and aramid fiber are modified using a silane coupling agent to improve their compatibility with nylon resin and enhance the mechanical properties and durability of the composite material. The treated glass fiber and aramid fiber are mixed to obtain a mixed fiber for later use; The mixed material A is put into the twin-screw extruder from the main feeding port, and the mixed fiber is put into the twin-screw extruder from the side feeding port. The heat-resistant reinforcing masterbatch is added to the part where the internal temperature of the twin-screw extruder is between 220°C and 245°C. The final material is obtained after melting, extrusion, cooling, drying and cutting. The controlled temperature of each section of the twin-screw extruder (from the feeding port to the die outlet) is 210°C, 240°C, 265°C, 255°C, 250°C, 240°C, 240°C, 240°C, 240°C, 240°C, and 240°C. Example 2

[0023] See also Figure 1 、 Figure 2 and Figure 3 , a high heat-resistant glass fiber reinforced nylon material, comprising the following components in parts by weight: nylon resin: 67 parts; Glass fiber: 5 parts; Aramid fiber: 5 parts; Heat-resistant reinforcing masterbatch: 15 parts; Flame retardant: 12 parts; Lubricant: 2 parts; Stabilizer: 2 parts; Catalyst: 3 parts; Coupling agent: 0.2 parts; The preparation method of the heat-resistant reinforcing masterbatch comprises: mixing zinc oxide and cage-type polysilsesquioxane to react, so that the cage-type polysilsesquioxane forms a coating layer on the surface of the zinc oxide, washing and drying the encapsulated composite of zinc oxide and cage-type polysilsesquioxane, removing unreacted raw materials, preparing sufficient amounts of styrene-acrylonitrile copolymer, polyphenylene ether, lubricant and stabilizer for mixing, placing the mixture and chopped carbon fibers into a twin-screw extruder, adding the composite of zinc oxide and cage-type polysilsesquioxane at a position where the internal temperature of the twin-screw extruder is between 220° C. and 245° C., and obtaining the heat-resistant reinforcing masterbatch through melting, extrusion, cooling, drying and cutting, wherein the partition control temperature of the twin-screw extruder (from the feed port to the die outlet) is 210° C., 245° C., 255° C., 245° C., 230° C., 230° C., 220° C. and 220° C., and the material residence time in the barrel is 2 minutes; During the preparation of heat-resistant reinforcing masterbatch, although the composite of zinc oxide and cage-type polysilsesquioxane is wrapped by the cage-type polysilsesquioxane shell in a high-temperature environment, excessively high temperature will destroy its internal structure, thereby causing the composite of zinc oxide and cage-type polysilsesquioxane to agglomerate, resulting in poor heat resistance and thermal stability of the prepared heat-resistant reinforcing masterbatch. Therefore, the temperature should be controlled not to be too high during the preparation process. The steps of the preparation method are as follows: Step 1: Prepare nylon resin, glass fiber and aramid fiber in the required proportions and dry them to remove moisture at a drying temperature of 50-80°C for 4 hours; Step 2: mixing the glass fiber and the aramid fiber in a weight ratio of 1:1 to obtain a mixed fiber; Step 3: Add nylon resin, flame retardant, lubricant, stabilizer and catalyst into a high-speed mixer, and fully mix all the materials in the high-speed mixer to obtain mixed material A; Step 4: Place the mixed material A into the twin-screw extruder through the main feed port, and place the mixed fiber into the twin-screw extruder through the side feed port. During the melting process, add the heat-resistant reinforcing masterbatch to the part of the twin-screw extruder where the internal temperature is between 220℃ and 245℃. After melt blending, extrude the mixture into the mold for shaping. Step 5: After the product is cooled and shaped, dry it; Step 6: Cut the molded product to obtain the final high heat-resistant glass fiber reinforced nylon material; Furthermore, in the raw material preparation stage, 60 parts of nylon resin, 12 parts of heat-resistant reinforcing masterbatch, 10 parts of flame retardant, 3 parts of lubricant, 3 parts of stabilizer, and 3 parts of catalyst were prepared, the nylon resin was dried in an 80° C. environment for 4 hours, and the materials except the heat-resistant reinforcing masterbatch were placed in a high-speed mixer and fully mixed to obtain mixed material A for standby use; Prepare 6 parts of glass fiber and 0.4 parts of coupling agent, use silane coupling agent to modify the surface of the glass fiber to improve its compatibility with nylon resin and enhance the mechanical properties and durability of the composite material, and set aside; The mixed material A is put into the twin-screw extruder from the main feeding port, and the mixed fiber is put into the twin-screw extruder from the side feeding port. The heat-resistant reinforcing masterbatch is added to the part where the internal temperature of the twin-screw extruder is between 220°C and 245°C. The final material is obtained after melting, extrusion, cooling, drying and cutting. The controlled temperature of each section of the twin-screw extruder (from the feeding port to the die outlet) is 210°C, 240°C, 265°C, 255°C, 250°C, 240°C, 240°C, 240°C, 240°C, 240°C, and 240°C. Example 3

[0024] See also Figure 1 、 Figure 2 and Figure 3 , a high heat-resistant glass fiber reinforced nylon material, comprising the following components in parts by weight: nylon resin: 67 parts; Glass fiber: 5 parts; Aramid fiber: 5 parts; Heat-resistant reinforcing masterbatch: 15 parts; Flame retardant: 12 parts; Lubricant: 2 parts; Stabilizer: 2 parts; Catalyst: 3 parts; Coupling agent: 0.2 parts; The preparation method of the heat-resistant reinforcing masterbatch comprises: mixing zinc oxide and cage-type polysilsesquioxane to react, so that the cage-type polysilsesquioxane forms a coating layer on the surface of the zinc oxide, washing and drying the encapsulated composite of zinc oxide and cage-type polysilsesquioxane, removing unreacted raw materials, preparing sufficient amounts of styrene-acrylonitrile copolymer, polyphenylene ether, lubricant and stabilizer for mixing, placing the mixture and chopped carbon fibers into a twin-screw extruder, adding the composite of zinc oxide and cage-type polysilsesquioxane at a position where the internal temperature of the twin-screw extruder is between 220° C. and 245° C., and obtaining the heat-resistant reinforcing masterbatch through melting, extrusion, cooling, drying and cutting, wherein the partition control temperature of the twin-screw extruder (from the feed port to the die outlet) is 210° C., 245° C., 255° C., 245° C., 230° C., 230° C., 220° C. and 220° C., and the material residence time in the barrel is 2 minutes; During the preparation of heat-resistant reinforcing masterbatch, although the composite of zinc oxide and cage-type polysilsesquioxane is wrapped by the cage-type polysilsesquioxane shell in a high-temperature environment, excessively high temperature will destroy its internal structure, thereby causing the composite of zinc oxide and cage-type polysilsesquioxane to agglomerate, resulting in poor heat resistance and thermal stability of the prepared heat-resistant reinforcing masterbatch. Therefore, the temperature should be controlled not to be too high during the preparation process. The steps of the preparation method are as follows: Step 1: Prepare nylon resin, glass fiber and aramid fiber in the required proportions and dry them to remove moisture at a drying temperature of 50-80°C for 4 hours; Step 2: mixing the glass fiber and the aramid fiber in a weight ratio of 1:1 to obtain a mixed fiber; Step 3: Add nylon resin, flame retardant, lubricant, stabilizer and catalyst into a high-speed mixer, and fully mix all the materials in the high-speed mixer to obtain mixed material A; Step 4: Place the mixed material A into the twin-screw extruder through the main feed port, and place the mixed fiber into the twin-screw extruder through the side feed port. During the melting process, add the heat-resistant reinforcing masterbatch to the part of the twin-screw extruder where the internal temperature is between 220℃ and 245℃. After melt blending, extrude the mixture into the mold for shaping. Step 5: After the product is cooled and shaped, dry it; Step 6: Cut the molded product to obtain the final high heat-resistant glass fiber reinforced nylon material; Furthermore, in the raw material preparation stage, 60 parts of nylon resin, 10 parts of flame retardant, 3 parts of lubricant, 3 parts of stabilizer, and 3 parts of catalyst were prepared, the nylon resin was dried at 80° C. for 4 hours, and the materials were placed in a high-speed mixer and fully mixed to obtain mixed material A for standby use; 6 parts of glass fiber, 6 parts of aramid fiber and 0.4 parts of coupling agent are prepared, and the surfaces of the glass fiber and aramid fiber are modified using a silane coupling agent to improve their compatibility with nylon resin and enhance the mechanical properties and durability of the composite material. The treated glass fiber and aramid fiber are mixed to obtain a mixed fiber for later use; The mixed material A is put into the twin-screw extruder from the main feeding port, and the mixed fiber is put into the twin-screw extruder from the side feeding port. The final material is obtained after melting, extrusion, cooling, drying and cutting. The controlled temperature of each section of the twin-screw extruder (from the feeding port to the die outlet) is 210°C, 240°C, 265°C, 255°C, 250°C, 240°C, 240°C, 240°C, 240°C, 240°C, and 240°C. Example 4

[0025] See also Figure 1 、 Figure 2 and Figure 3 , a high heat-resistant glass fiber reinforced nylon material, comprising the following components in parts by weight: nylon resin: 67 parts; Glass fiber: 5 parts; Aramid fiber: 5 parts; Heat-resistant reinforcing masterbatch: 15 parts; Flame retardant: 12 parts; Lubricant: 2 parts; Stabilizer: 2 parts; Catalyst: 3 parts; Coupling agent: 0.2 parts; The preparation method of the heat-resistant reinforcing masterbatch comprises: mixing zinc oxide and cage-type polysilsesquioxane to react, so that the cage-type polysilsesquioxane forms a coating layer on the surface of the zinc oxide, washing and drying the encapsulated composite of zinc oxide and cage-type polysilsesquioxane, removing unreacted raw materials, preparing sufficient amounts of styrene-acrylonitrile copolymer, polyphenylene ether, lubricant and stabilizer for mixing, placing the mixture and chopped carbon fibers into a twin-screw extruder, adding the composite of zinc oxide and cage-type polysilsesquioxane at a position where the internal temperature of the twin-screw extruder is between 220° C. and 245° C., and obtaining the heat-resistant reinforcing masterbatch through melting, extrusion, cooling, drying and cutting, wherein the partition control temperature of the twin-screw extruder (from the feed port to the die outlet) is 210° C., 245° C., 255° C., 245° C., 230° C., 230° C., 220° C. and 220° C., and the material residence time in the barrel is 2 minutes; During the preparation of heat-resistant reinforcing masterbatch, although the composite of zinc oxide and cage-type polysilsesquioxane is wrapped by the cage-type polysilsesquioxane shell in a high-temperature environment, excessively high temperature will destroy its internal structure, thereby causing the composite of zinc oxide and cage-type polysilsesquioxane to agglomerate, resulting in poor heat resistance and thermal stability of the prepared heat-resistant reinforcing masterbatch. Therefore, the temperature should be controlled not to be too high during the preparation process. The steps of the preparation method are as follows: Step 1: Prepare nylon resin, glass fiber and aramid fiber in the required proportions and dry them to remove moisture at a drying temperature of 50-80°C for 4 hours; Step 2: mixing the glass fiber and the aramid fiber in a weight ratio of 1:1 to obtain a mixed fiber; Step 3: Add nylon resin, flame retardant, lubricant, stabilizer and catalyst into a high-speed mixer, and fully mix all the materials in the high-speed mixer to obtain mixed material A; Step 4: Place the mixed material A into the twin-screw extruder through the main feed port, and place the mixed fiber into the twin-screw extruder through the side feed port. During the melting process, add the heat-resistant reinforcing masterbatch to the part of the twin-screw extruder where the internal temperature is between 220℃ and 245℃. After melt blending, extrude the mixture into the mold for shaping. Step 5: After the product is cooled and shaped, dry it; Step 6: Cut the molded product to obtain the final high heat-resistant glass fiber reinforced nylon material; Furthermore, in the process of preparing the heat-resistant enhanced masterbatch, the cage-type polysilsesquioxane is not added, and the other raw materials and their weight parts remain unchanged to prepare the heat-resistant enhanced masterbatch; In the raw material preparation stage, 60 parts of nylon resin, 12 parts of heat-resistant reinforcing masterbatch, 10 parts of flame retardant, 3 parts of lubricant, 3 parts of stabilizer, and 3 parts of catalyst were prepared. The nylon resin was dried at 80°C for 4 hours. The materials except the heat-resistant reinforcing masterbatch were placed in a high-speed mixer and fully mixed to obtain mixed material A for standby use. 6 parts of glass fiber, 6 parts of aramid fiber and 0.4 parts of coupling agent are prepared, and the surfaces of the glass fiber and aramid fiber are modified using a silane coupling agent to improve their compatibility with nylon resin and enhance the mechanical properties and durability of the composite material. The treated glass fiber and aramid fiber are mixed to obtain a mixed fiber for later use; The mixed material A is put into the twin-screw extruder from the main feeding port, and the mixed fiber is put into the twin-screw extruder from the side feeding port. The heat-resistant reinforcing masterbatch is added to the part where the internal temperature of the twin-screw extruder is between 220°C and 245°C. The final material is obtained after melting, extrusion, cooling, drying and cutting. The controlled temperature of each section of the twin-screw extruder (from the feeding port to the die outlet) is 210°C, 240°C, 265°C, 255°C, 250°C, 240°C, 240°C, 240°C, 240°C, 240°C, and 240°C. Example 5

[0026] See also Figure 1 、 Figure 2 and Figure 3 , a high heat-resistant glass fiber reinforced nylon material, comprising the following components in parts by weight: nylon resin: 67 parts; Glass fiber: 5 parts; Aramid fiber: 5 parts; Heat-resistant reinforcing masterbatch: 15 parts; Flame retardant: 12 parts; Lubricant: 2 parts; Stabilizer: 2 parts; Catalyst: 3 parts; Coupling agent: 0.2 parts; The preparation method of the heat-resistant reinforcing masterbatch comprises: mixing zinc oxide and cage-type polysilsesquioxane to react, so that the cage-type polysilsesquioxane forms a coating layer on the surface of the zinc oxide, washing and drying the encapsulated composite of zinc oxide and cage-type polysilsesquioxane, removing unreacted raw materials, preparing sufficient amounts of styrene-acrylonitrile copolymer, polyphenylene ether, lubricant and stabilizer for mixing, placing the mixture and chopped carbon fibers into a twin-screw extruder, adding the composite of zinc oxide and cage-type polysilsesquioxane at a position where the internal temperature of the twin-screw extruder is between 220° C. and 245° C., and obtaining the heat-resistant reinforcing masterbatch through melting, extrusion, cooling, drying and cutting, wherein the partition control temperature of the twin-screw extruder (from the feed port to the die outlet) is 210° C., 245° C., 255° C., 245° C., 230° C., 230° C., 220° C. and 220° C., and the material residence time in the barrel is 2 minutes; During the preparation of heat-resistant reinforcing masterbatch, although the composite of zinc oxide and cage-type polysilsesquioxane is wrapped by the cage-type polysilsesquioxane shell in a high-temperature environment, excessively high temperature will destroy its internal structure, thereby causing the composite of zinc oxide and cage-type polysilsesquioxane to agglomerate, resulting in poor heat resistance and thermal stability of the prepared heat-resistant reinforcing masterbatch. Therefore, the temperature should be controlled not to be too high during the preparation process. The steps of the preparation method are as follows: Step 1: Prepare nylon resin, glass fiber and aramid fiber in the required proportions and dry them to remove moisture at a drying temperature of 50-80°C for 4 hours; Step 2: mixing the glass fiber and the aramid fiber in a weight ratio of 1:1 to obtain a mixed fiber; Step 3: Add nylon resin, flame retardant, lubricant, stabilizer and catalyst into a high-speed mixer, and fully mix all the materials in the high-speed mixer to obtain mixed material A; Step 4: Place the mixed material A into the twin-screw extruder through the main feed port, and place the mixed fiber into the twin-screw extruder through the side feed port. During the melting process, add the heat-resistant reinforcing masterbatch to the part of the twin-screw extruder where the internal temperature is between 220℃ and 245℃. After melt blending, extrude the mixture into the mold for shaping. Step 5: After the product is cooled and shaped, dry it; Step 6: Cut the molded product to obtain the final high heat-resistant glass fiber reinforced nylon material; Furthermore, in the preparation process of the heat-resistant enhanced masterbatch, zinc oxide is not added, and the other components and their weight portions remain unchanged to prepare the heat-resistant enhanced masterbatch; In the raw material preparation stage, 60 parts of nylon resin, 12 parts of heat-resistant reinforcing masterbatch, 10 parts of flame retardant, 3 parts of lubricant, 3 parts of stabilizer, and 3 parts of catalyst were prepared. The nylon resin was dried at 80°C for 4 hours. The materials except the heat-resistant reinforcing masterbatch were placed in a high-speed mixer and fully mixed to obtain mixed material A for standby use. 6 parts of glass fiber, 6 parts of aramid fiber and 0.4 parts of coupling agent are prepared, and the surfaces of the glass fiber and aramid fiber are modified using a silane coupling agent to improve their compatibility with nylon resin and enhance the mechanical properties and durability of the composite material. The treated glass fiber and aramid fiber are mixed to obtain a mixed fiber for later use; The mixed material A is put into the twin-screw extruder from the main feeding port, and the mixed fiber is put into the twin-screw extruder from the side feeding port. The heat-resistant reinforcing masterbatch is added to the part where the internal temperature of the twin-screw extruder is between 220°C and 245°C. The final material is obtained after melting, extrusion, cooling, drying and cutting. The controlled temperature of each section of the twin-screw extruder (from the feeding port to the die outlet) is 210°C, 240°C, 265°C, 255°C, 250°C, 240°C, 240°C, 240°C, 240°C, 240°C, and 240°C. Example 6

[0027] See also Figure 1 、 Figure 2 and Figure 3 , a high heat-resistant glass fiber reinforced nylon material, comprising the following components in parts by weight: nylon resin: 67 parts; Glass fiber: 5 parts; Aramid fiber: 5 parts; Heat-resistant reinforcing masterbatch: 15 parts; Flame retardant: 12 parts; Lubricant: 2 parts; Stabilizer: 2 parts; Catalyst: 3 parts; Coupling agent: 0.2 parts; The preparation method of the heat-resistant reinforcing masterbatch comprises: mixing zinc oxide and cage-type polysilsesquioxane to react, so that the cage-type polysilsesquioxane forms a coating layer on the surface of the zinc oxide, washing and drying the encapsulated composite of zinc oxide and cage-type polysilsesquioxane, removing unreacted raw materials, preparing sufficient amounts of styrene-acrylonitrile copolymer, polyphenylene ether, lubricant and stabilizer for mixing, placing the mixture and chopped carbon fibers into a twin-screw extruder, adding the composite of zinc oxide and cage-type polysilsesquioxane at a position where the internal temperature of the twin-screw extruder is between 220° C. and 245° C., and obtaining the heat-resistant reinforcing masterbatch through melting, extrusion, cooling, drying and cutting, wherein the partition control temperature of the twin-screw extruder (from the feed port to the die outlet) is 210° C., 245° C., 255° C., 245° C., 230° C., 230° C., 220° C. and 220° C., and the material residence time in the barrel is 2 minutes; During the preparation of heat-resistant reinforcing masterbatch, although the composite of zinc oxide and cage-type polysilsesquioxane is wrapped by the cage-type polysilsesquioxane shell in a high-temperature environment, excessively high temperature will destroy its internal structure, thereby causing the composite of zinc oxide and cage-type polysilsesquioxane to agglomerate, resulting in poor heat resistance and thermal stability of the prepared heat-resistant reinforcing masterbatch. Therefore, the temperature should be controlled not to be too high during the preparation process. The steps of the preparation method are as follows: Step 1: Prepare nylon resin, glass fiber and aramid fiber in the required proportions and dry them to remove moisture at a drying temperature of 50-80°C for 4 hours; Step 2: mixing the glass fiber and the aramid fiber in a weight ratio of 1:1 to obtain a mixed fiber; Step 3: Add nylon resin, flame retardant, lubricant, stabilizer and catalyst into a high-speed mixer, and fully mix all the materials in the high-speed mixer to obtain mixed material A; Step 4: Place the mixed material A into the twin-screw extruder through the main feed port, and place the mixed fiber into the twin-screw extruder through the side feed port. During the melting process, add the heat-resistant reinforcing masterbatch to the part of the twin-screw extruder where the internal temperature is between 220℃ and 245℃. After melt blending, extrude the mixture into the mold for shaping. Step 5: After the product is cooled and shaped, dry it; Step 6: Cut the molded product to obtain the final high heat-resistant glass fiber reinforced nylon material; Furthermore, in the process of preparing the heat-resistant enhanced masterbatch, zinc oxide and cage-type polysilsesquioxane are not added, and other raw materials and their weight portions remain unchanged to prepare the heat-resistant enhanced masterbatch; In the raw material preparation stage, 60 parts of nylon resin, 12 parts of heat-resistant reinforcing masterbatch, 10 parts of flame retardant, 3 parts of lubricant, 3 parts of stabilizer and 3 parts of catalyst were prepared, the nylon resin was dried at 80°C for 4 hours, and the materials except the heat-resistant reinforcing masterbatch were placed in a high-speed mixer and fully mixed to obtain mixed material A for standby use; 6 parts of glass fiber, 6 parts of aramid fiber and 0.4 parts of coupling agent are prepared, and the surfaces of the glass fiber and aramid fiber are modified using a silane coupling agent to improve their compatibility with nylon resin and enhance the mechanical properties and durability of the composite material. The treated glass fiber and aramid fiber are mixed to obtain a mixed fiber for later use; The mixed material A is put into the twin-screw extruder from the main feeding port, and the mixed fiber is put into the twin-screw extruder from the side feeding port. The heat-resistant reinforcing masterbatch is added to the part where the internal temperature of the twin-screw extruder is between 220°C and 245°C. The final material is obtained after melting, extrusion, cooling, drying and cutting. The controlled temperature of each section of the twin-screw extruder (from the feeding port to the die outlet) is 210°C, 240°C, 265°C, 255°C, 250°C, 240°C, 240°C, 240°C, 240°C, 240°C, and 240°C.

[0028] Performance Testing The pelletized samples of Examples 1-6 were injection molded on an injection molding machine and tested according to relevant standards. The heat resistance test method was to gradually heat the prepared specimens and observe the deformation of the specimens during the heating process. The results are as follows: performance unit Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 tensile strength MPa 187 178 180 184 183 182 Bending strength MPa 269 261 267 268 267 266 flexural modulus MPa 8530 8319 8480 8460 8470 8430 Heat deformation temperature (1.80MPa) ℃ 271 256 244 263 265 260 Notched impact strength <![CDATA[KJ / m 2 ]]> 42.7 35.1 39.4 41.1 41.3 40.5 Vertical combustion level / FV-0 FV-0 FV-0 FV-0 FV-0 FV-0 Working principle: prepare 30 to 80 parts of nylon resin, 5 to 20 parts of glass fiber, 5 to 20 parts of aramid fiber, 10 to 20 parts of heat-resistant reinforcing masterbatch, 10 to 20 parts of flame retardant, 2 to 4 parts of lubricant, 2 to 4 parts of stabilizer, 1 to 3 parts of catalyst, 0.1 to 0.5 parts of coupling agent, wherein the weight ratio of glass fiber and aramid fiber is 1:1, the weight ratio of aluminum hydroxide and melamine cyanurate is 2:3 as flame retardant, PA66 as nylon resin, silicone masterbatch as lubricant, iron hydroxide as catalyst, silane coupling agent as coupling agent, preparation process of heat-resistant reinforcing masterbatch The method comprises the following steps: mixing zinc oxide and cage-type polysilsesquioxane to react, so that the cage-type polysilsesquioxane forms a coating layer on the surface of the zinc oxide; washing and drying the encapsulated composite of zinc oxide and cage-type polysilsesquioxane to remove unreacted raw materials; preparing sufficient amounts of styrene-acrylonitrile copolymer, polyphenylene ether, lubricant, and stabilizer for mixing; placing the mixture and chopped carbon fibers into a twin-screw extruder; adding the composite of zinc oxide and cage-type polysilsesquioxane at a position where the internal temperature of the twin-screw extruder is between 220° C. and 245° C.; and obtaining a heat-resistant reinforcing masterbatch through melting, extrusion, cooling, drying, and cutting. All raw materials except glass fiber, aramid fiber, heat-resistant reinforcing masterbatch and coupling agent are placed in a high-speed mixer and fully mixed. The glass fiber, aramid fiber and coupling agent are fully mixed and fed into a twin-screw extruder through a main feed port and a side feed port respectively. The heat-resistant reinforcing masterbatch is added to a part of the twin-screw extruder where the internal temperature is between 220°C and 245°C. After melt extrusion, cooling, drying and cutting, the final product, high-heat-resistant glass fiber reinforced nylon material, is obtained.

[0029] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be included therein. Any reference sign in a claim should not be construed as limiting the claim to which it relates.

Claims

1. A high heat-resistant glass fiber reinforced nylon material, characterized by: The invention comprises the following components by weight: 30 to 80 parts of nylon resin; Glass fiber: 5 to 20 parts; Aramid fiber: 5 to 20 parts; Heat-resistant reinforcing masterbatch: 10 to 20 parts; Flame retardant: 10 to 20 parts; Lubricant: 2 to 4 parts; Stabilizer: 2 to 4 parts; Catalyst: 1 to 3 parts; Coupling agent: 0.1 to 0.5 parts; The preparation method of the heat-resistant enhanced masterbatch is as follows: zinc oxide and cage-type polysilsesquioxane are mixed and reacted to form a coating layer of cage-type polysilsesquioxane on the surface of zinc oxide, the encapsulated composite of zinc oxide and cage-type polysilsesquioxane is washed and dried, unreacted raw materials are removed, sufficient amounts of styrene-acrylonitrile copolymer, polyphenylene ether, lubricant and stabilizer are prepared for mixing, the mixture and long-cut carbon fiber are put into a twin-screw extruder, the composite of zinc oxide and cage-type polysilsesquioxane is added to a part where the internal temperature of the twin-screw extruder is between 220° C. and 245° C., and the heat-resistant enhanced masterbatch is obtained through melting, extrusion, cooling, drying and cutting, wherein the partition control temperature of the twin-screw extruder is 210° C., 245° C., 255° C., 245° C., 230° C., 230° C., 220° C., and 220° C., and the material stays in the barrel for 2 minutes; In the process of preparing heat-resistant enhanced masterbatch, although the composite of zinc oxide and cage-type polysilsesquioxane is wrapped by the cage-type polysilsesquioxane shell in a high temperature environment, excessively high temperature will destroy its internal structure, thereby aggravating the agglomeration phenomenon of the composite of zinc oxide and cage-type polysilsesquioxane, resulting in poor heat resistance and thermal stability of the prepared heat-resistant enhanced masterbatch. The temperature needs to be controlled not to be too high during the preparation process.

2. The high heat-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The nylon resin is one of PA6 and PA66 or a mixture thereof.

3. The high heat-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The glass fiber is alkali-free glass fiber, the aramid fiber is para-aramid fiber, and the weight ratio of the glass fiber to the aramid fiber is 1:

1.

4. The high heat-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The flame retardant is a mixture of aluminum hydroxide and melamine cyanurate. The flame retardant properties of the material are improved and the generation of harmful substances is reduced by using two flame retardants with different action systems.

5. The high heat-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The lubricant is a silicone masterbatch, which is used to improve the uniformity of the material and enhance the performance and service life of the material.

6. The high heat-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The stabilizer is a copper salt masterbatch, which is used to prevent oxidative degradation during processing and can also improve the heat resistance of the material.

7. The high heat-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The catalyst is iron hydroxide, which catalyzes a specific reaction of the mixed materials in a twin-screw extruder.

8. The high heat-resistant glass fiber reinforced nylon material according to claim 1, characterized in that: The coupling agent is a silane coupling agent.

9. A method for preparing a high heat-resistant glass fiber reinforced nylon material, applicable to a high heat-resistant glass fiber reinforced nylon material according to any one of claims 1 to 8, characterized in that: The steps of the preparation method are as follows: Step 1: Prepare nylon resin, glass fiber and aramid fiber in the required proportion, and dry them to remove moisture. The drying temperature is 50-80°C and the drying time is 4 hours; Step 2: Mixing glass fiber and aramid fiber in a weight ratio of 1:1 to obtain mixed fiber; Step 3: Add nylon resin, flame retardant, lubricant, stabilizer and catalyst into a high-speed mixer, and fully mix all the materials in the high-speed mixer to obtain mixed material A; Step 4: Put the mixed material A into the twin-screw extruder through the main feed port, and put the mixed fiber into the twin-screw extruder from the side feed port. During the melting process, add the heat-resistant reinforcing masterbatch to the part of the twin-screw extruder where the internal temperature is between 220℃ and 245℃, and extrude it into the mold for shaping after melt blending; Step 5: After the product is cooled and shaped, dry it; Step 6: Cut the molded product to obtain the final high heat-resistant glass fiber reinforced nylon material.

10. The method for preparing a high heat-resistant glass fiber reinforced nylon material according to claim 9, characterized in that: When the glass fiber and the aramid fiber are mixed, a silane coupling agent is used to modify the surface of the glass fiber and the aramid fiber to improve their compatibility with the nylon resin and enhance the mechanical properties and durability of the composite material; The flame retardant is a mixture of melamine cyanurate and aluminum hydroxide. Before use, a coupling agent is required to modify the aluminum hydroxide to improve its dispersibility and mechanical properties in nylon. Treatment of melamine cyanurate requires drying at 100°C in a vacuum environment for 8 hours.